Does integrating nonurgent, clinically significant radiology alerts within the electronic health record impact closed-loop communication and follow-up?. (2nd September 2015) - O'Connor, Stacy D; Dalal, Anuj K; Sahni, V Anik; Lacson, Ronilda; Khorasani, Ramin
Abstract: Objective To assess whether integrating critical result management software—Alert Notification of Critical Results (ANCR)—with an electronic health record (EHR)-based results management application impacts closed-loop communication and follow-up of nonurgent, clinically significant radiology results by primary care providers (PCPs). Materials and Methods This institutional review board-approved study was conducted at a large academic medical center. Postintervention, PCPs could acknowledge nonurgent, clinically significant ANCR-generated alerts ("alerts") within ANCR or the EHR. Primary outcome was the proportion of alerts acknowledged via EHR over a 24-month postintervention. Chart abstractions for a random sample of alerts 12 months preintervention and 24 months postintervention were reviewed, and the follow-up rate of actionable alerts (eg, performing follow-up imaging, administering antibiotics) was estimated. Pre- and postintervention rates were compared using the Fisher exact test. Postintervention follow-up rate was compared for EHR-acknowledged alerts vs ANCR. Results Five thousand nine hundred and thirty-one alerts were acknowledged by 171 PCPs, with 100% acknowledgement (consistent with expected ANCR functionality). PCPs acknowledged 16% (688 of 4428) of postintervention alerts in the EHR, with the remaining in ANCR. Follow-up was documented for 85 of 90 (94%; 95% CI, 88%-98%) preintervention and 79 of 84 (94%; 95% CI, 87%-97%) postintervention alerts ( P > .99). Postintervention, 11 of 14 (79%; 95% CI, 52%-92%) alerts were acknowledged via EHR and 68 of 70 (97%; 95% CI, 90%-99%) in ANCR had follow-up ( P = .03). Conclusions Integrating ANCR and EHR provides an additional workflow for acknowledging nonurgent, clinically significant results without significant change in rates of closed-loop communication or follow-up of alerts.